THE EFFECTIVENESS OF SCRAPMOD AS A LEARNING MEDIA TO IMPROVE STUDENTS’ LEARNING OUTCOMES - Tiara Yusi Destari; Rusly Hidayah (Jurnal Tadris Kimiya, 2019)
This study aims to determine the effect of scrapmod which is a learning media which is a combination of scrapbook and moly mod to improve cognitive learning outcomes of students on molecular geometry. This study uses an R & D method (Research & Development) which is conducted only to a limited trial. The limited trials were conducted using a one-group pretest-posttest design. The pretest and posttest values obtained must be normalized using the Kolmogorov Smirnov test, then the N-Gain value is evaluated to obtain the improvement in cognitive learning outcomes of each student. Cognitive learning outcomes of students discussed increased if posttest values are greater than the pretest. The limited trial was conducted on 33 students of class XI of SMAN 1 Porong, Sidoarjo. The method of collecting data is done by using questionnaires, observations, and tests. The average percentage of the N-Gain score obtained is 0.6, which means it falls into the medium category. This shows that the use of scarpmod as a learning media on molecular geometry gives a positive response that can improve students' cognitive learning outcomes.